Preload and friction in an implant-abutment-screw complex including a carbon-coated titanium alloy abutment screw: an in vitro study - K. Sagheb; C.-I. Görgen; S. Döll; I. Schmidtmann; S. Wentaschek (SpringerOpen, 2023)
Abstract Purpose An experimental approach was designed to measure the preload force, the coefficient of friction and the component of the tightening torque that is needed to surmount the thread-friction in an implant-abutment-screw complex that includes a carbon-coated screw. With the determined preload values the coefficient of friction was calculated. Methods 25 unused complexes, containing an implant, an abutment and a carbon-coated titanium alloy abutment screw, were tested. A custom load frame with two load cells and associated electronics was used. The threads were not lubricated. All abutment screws were torqued ten times to 25 Ncm. The produced preload values and a force that was proportional to the thread-friction component of the tightening torque were recorded. Results Mean preload values decreased significantly with the number of repetitions (p < 0.0001) from initially 329.9 N ± 33.3 (range 255.7 to 383.9) to 253.7 N ± 36.8 (range 200.1 to 332.5) for the last tightening procedure. The corresponding change in the calculated coefficient of friction was 0.33 ± 0.04 (range 0.28 to 0.43) to 0.44 ± 0.07 (range 0.32 to 0.56). For the thread-friction no corresponding trend for consecutive tightening repetitions could be noticed. Conclusions In the investigated implant-abutment units, repeated use of a coated abutment screw appears to increase the friction of the screw head and thereby decrease the preload. These results indicate that a pre-used coated implant-abutment-screw will fail reaching optimal screw preload. Graphical abstract